TREND LINEAR WATER USE APPLICATIONS IN ENVIRONMENTAL PAM HOUSEHOLDS USING PASCAL PROGRAMMING 5.0 - Rhama Rhama; Jalinas, SKom, MM Jalinas, SKom, MM (Jurnal Sistem Informasi, 2005)
In the statistical sciences whose names are known Linear Trend. This linear trend can be used to predict the value of water usage each month. With Linear Trend is to be obtained value of water usage each month. These values describe the state of water consumption in each month.  In scientific writing, the writer discusses only calculate linear trend with the least square method in drinking water consumption (PAM).